PENGARUH MOBILE WEBSITE DAN ADVERTISING RECOGNITION TERHADAP ONLINE WILLINGNESS TO BUY PRODUK LOKAL GEOFF MAX - Reza Ahmad Ferdiansyah, - (2023)
This study aims to obtain an overview and influence of mobile websites and advertising recognition on online willingness to buy local products Geoff Max's. This research uses descriptive and verification methods with a quantitative approach. The population in this study amounted to 68.500 with a sample of 200 respondents who were local.communion Instagram followers using a simple random sampling technique. The data were processed statistically using the Structural Equation Modeling (SEM) method. The findings in this study found that mobile websites and advertising recognition have a positive and significant influence on online willingness to buy, this is indicated by the critical ratio value which is greater than the minimum value, meaning that there is a positive and significant influence between the mobile website and advertising recognition variables. on online willingness to buy simultaneously. It can be assumed that the better the company pays attention to mobile websites and advertising recognition, the better the online willingness to buy that appears to consumers for these companies. The highest contribution given by the mobile website variable in forming online willingness to buy is trust and the lowest mobile website dimension in forming online willingness to buy is attachment. The dimension of advertising recognition that has the highest contribution in shaping online willingness to buy is impact and the lowest in forming online willingness to buy is empathy.